ASSESSMENT OF THE FUNCTIONAL PREPAREDNESS OF THE WOMEN’S NATIONAL TEAM OF RUSSIA IN THAI BOXING - Stepanov, M.Yu.; Lukina, A.M.; Grakhov, I.A.; Mustaeva, V.V. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to assess the functional readiness of the Russian women’s national team in Thai boxing. Methods and structure of the study. The experiment took place from 03/12/2022 to 03/26/2022 at the Federal Sports Center "Yug Sport" in Kislovodsk. The 1st and 2nd numbers of the women’s national team of Russia in the amount of 21 people took part in the training event. Correlation analysis of the means used: in the form of test training, current examination, no-load testing, was compared with an expert assessment of the leading specialists of the Russian national team. Results and conclusions. A strong association with expert opinion was found with anaerobic hand performance recorded on the Monark Ergomedic 894E bicycle ergometer. Medium Connectivity is an exercise with BlazePod sensors in focus mode. Low connection in exercises: barbell, pull-ups on the horizontal bar, % fat, % muscle and the sum of the rating points. The rest of the tests were unreliable. The training process, with the inclusion of test tasks, motivate athletes to perform the load with dedication, and the proposed control over preparedness in the form of a set of rating points allows you to visually assess the profile of an athlete’s preparedness, identifying his strengths and weaknesses. However, the selection of informative exercises for the preparation of highly qualified Thai boxers requires additional research.